Job involvement for workers and its influence in Crystallize organizational Identification (An analytical research of the opinions of a sample of workers in the Middle East, the Iraqi Investment Bank) - احمد شهناز فاضل (Journal of Economics and Administrative Sciences, 2016)
Abstract: The current research is aimed at analyzing the impact of the dimensions of Job involvement of all of (the enthusiasm, the Devotion, Assimilation ) in the Crystallize organizational Identification across the dimensions of (organizational loyalty, membership, similarities) and was named the Middle East, the Iraqi Investment Bank room to look as the research community of staff adopted in the bank, to be applied to a Random sample of (100) employees working in the said bank, and developed for the purposes of data collection, a questionnaire form included three axes covered (32) paragraph of the measure, which is included adopted Liekrt Quintet for the purpose of validating the key assumptions and sub-hypotheses, the most prominent prove the existence of the effect of a significance between Job involvement and organizational Identification. With the help of a number of statistical methods and software (spss-v20). The research found a set of conclusions including: 1- accept and clear to members of the sample to Twafaramqomat Job involvement for its removal after the arithmetic mean above-average record rate than can be said about a positive trend. 2- shows a positive relationship significant and influential statistically Job involvement mired in the development and strengthening of the organizational Identification seemed clear, boosting the efforts of members of the sample towards the principle of support and commitment. The study also recommended a set of recommendations which serve the purposes of research that developed for him and most importantly, the management of the bank to follow the modern administrative methods and take the necessary measures to deal with the workers, including increases the level of Astgrachm to work towards strengthening the organizational Identification have towards his organization